Flame-retardant coating agent for surface modification of wood paper and preparation method of flame-retardant coating agent

By combining modified epoxy resin and end-hydroxy hyperbranched polyester and combined with modified nanomaterials, the problems of insufficient adhesion and poor flame retardant properties of the electrostatic copy paper are solved, and a flame retardant coating agent with high adhesion, wear resistance and tortuous resistance are achieved, which is suitable for the modification of electrostatic copy paper.

CN119800765AActive Publication Date: 2025-04-11浙江鸿浩科技有限公司
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510120086.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-04-11
Estimated Expiration
2045-01-25

AI Technical Summary

Technical Problem

The flame retardant coating agent used in electrostatic copy paper in the prior art has problems such as insufficient adhesion, poor thermal stability, high volatility and poor adhesion of inorganic flame retardant, and it is difficult to meet the requirements of flame retardant performance, wear resistance and tortuous resistance at the same time.

Method used

Using a combination of modified epoxy resin, end-hydroxy hyperbranched polyester, modified material and isocyanate-based curing agent, a flame retardant coating agent with high adhesion, wear resistance and tortuous resistance are formed by modifying DGEBA resin, adding end-hydroxy hyperbranched polyester and modified nanomaterial.

Benefits of technology

It significantly improves the adhesion, wear resistance and tortuous resistance of the flame retardant coating agent on the surface of electrostatic copy paper, enhances the overall strength and flame retardant properties of the coating, and is suitable for use under different climatic conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of flame-retardant coating agents, and particularly relates to a flame-retardant coating agent for wood paper surface modification and a preparation method of the flame-retardant coating agent. The flame-retardant coating agent for wood paper surface modification comprises the following components in parts by weight: 70-80 parts of modified epoxy resin, 25-30 parts of hydroxyl-terminated hyperbranched polyester, 10-15 parts of a modified material and 20-30 parts of an isocyanate curing agent, the modified epoxy resin is prepared from a phase A and a phase B, wherein the phase A is DEM resin, and the phase B is a free radical photoinitiator and a polyether amine epoxy thermal curing agent. The flame-retardant coating agent prepared by the invention has excellent comprehensive performance and is suitable for being used as a surface coating agent of electrostatic copy paper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardant coating agents, and in particular relates to a flame retardant coating agent for surface modification of wood and paper and a preparation method thereof. Background Art

[0002] Electroscopy paper is a type of paper designed for copiers and laser printers. Its surface is specially treated to improve the quality of copying or printing and reduce the problem of multiple pages sticking together due to static electricity. Electroscopy paper usually has better smoothness, higher hardness and more uniform charge distribution, which helps improve the efficiency of equipment operation and output quality.

[0003] However, there are also some problems with the use of electrostatic copy paper: (1) For places where a large amount of documents are stored, such as archives, libraries, and data centers, using paper with certain flame retardant properties can reduce the risk of fire and slow the spread of fire, thereby providing more escape time and reducing property losses. (2) During the printing or copying process, if the coating adhesion is insufficient, it may cause image quality to deteriorate and even affect the operation of the equipment. In addition, during handling and storage, it can also avoid coating loss caused by friction and other reasons. (3) Abrasion resistance refers to the ability of the surface to resist wear. For documents that are frequently used or frequently turned over, abrasion resistance is an important consideration. Improving the abrasion resistance of copy paper can extend the life of the document, especially when important information needs to be preserved for a long time. (4) Copy paper is sometimes folded or curled, especially when bound into books. Good flex resistance helps to ensure the integrity of the paper under such operations and prevent damage or delamination. (5) Many copy papers may be used or stored under different climatic conditions. In environments with large temperature fluctuations, they may have problems such as poor flex resistance.

[0004] In the prior art, organic flame retardants are added to the coating agent on the surface of electrostatic copy paper to improve the flame retardancy, but when burned, toxic and corrosive gases are released, or there are disadvantages such as poor thermal stability and high volatility. The coating agent with inorganic flame retardants added has poor adhesion on the surface of electrostatic copy paper.

[0005] Therefore, there is an urgent need for a flame retardant coating agent for surface modification of wood and paper and a preparation method thereof. Summary of the invention

[0006] The purpose of the present invention is to provide a flame retardant coating agent for surface modification of wood and paper and a preparation method thereof.

[0007] In order to achieve the above object, the present invention provides the following technical solutions: A flame retardant coating agent for surface modification of wood and paper, comprising the following components in parts by weight: 70-80 parts of modified epoxy resin, 25-30 parts of terminal hydroxyl hyperbranched polyester, 10-15 parts of modified material and 20-30 parts of isocyanate curing agent; The raw materials for preparing the modified epoxy resin are phase A and phase B; wherein phase A is DEM resin, and phase B is a free radical photoinitiator and a polyetheramine epoxy thermal curing agent; The raw materials for preparing the DEM resin are: DGEBA resin, methacrylic acid, glycidyl methacrylate, p-hydroxyanisole, and benzyltriethylammonium chloride; the molar ratio of the DGEBA resin to methacrylic acid is (1.8-2.2):1; the amount of glycidyl methacrylate is 75-79% of the mass of the DGEBA resin; the amount of p-hydroxyanisole is 0.2-0.4% of the mass of the DGEBA resin; and the amount of benzyltriethylammonium chloride is 0.1-0.2% of the mass of the DGEBA resin.

[0008] Furthermore, the preparation method of the DEM resin comprises: firstly adding DGEBA resin and p-hydroxyanisole into a four-necked flask, then introducing nitrogen and heating to 60-65° C., pouring methacrylic acid into a constant pressure funnel, and dropping it into the four-necked flask, while slowly heating to 115-120° C., adding benzyltriethylammonium chloride and reacting for 2-3 hours, measuring the acid value of the system every 30-40 minutes during the reaction, until the acid value of the system drops below 3 mgKOH / g, and the reaction is terminated; cooling to 40-45° C., adding glycidyl methacrylate, stirring fully for 5-10 minutes, and then discharging to obtain the product.

[0009] Furthermore, the free radical photoinitiator is 184 initiator and TPO; the mass ratio of 184 initiator to DEM resin is (0.5-0.7):100; the mass ratio of TPO to DEM resin is (0.5-0.7):100.

[0010] The present invention can improve the adhesion of the flame retardant coating agent on the surface of electrostatic copy paper by modifying DGEBA. The epoxy groups in DGEBA (bisphenol A epoxy resin, E51) react with the carboxyl groups in methacrylic acid by ring-opening addition reaction, and the epoxy groups in methacrylic acid glycidyl ether react with the remaining carboxyl groups in the system by ring-opening addition reaction to generate more ester bonds. 184 initiator and TPO act as photoinitiators, which generate free radicals under light to initiate polymerization of unsaturated bonds in the system to form a three-dimensional network structure. By increasing polar functional groups and introducing methacrylic acid and methacrylic acid glycidyl ether, the polar functional groups in the resin are increased, and these polar groups can form hydrogen bonds or van der Waals forces with hydroxyl groups or other polar groups on the surface of paper, thereby enhancing adhesion.

[0011] Furthermore, the polyetheramine epoxy thermal curing agent has a brand name of D230, and the mass ratio of the polyetheramine epoxy thermal curing agent with a brand name of D230 to the DEM resin is (20-25):100.

[0012] Furthermore, the terminal hydroxyl hyperbranched polyester comprises a terminal hydroxyl hyperbranched polyester A, a terminal hydroxyl hyperbranched polyester B and a terminal hydroxyl hyperbranched polyester C in a weight ratio of 1: (1.2-1.4): (0.4-0.6); the terminal hydroxyl hyperbranched polyester A has a hydroxyl number of 10-12 / mol, a hydroxyl value of 600 mgKOH / g, and a molecular weight of 1100 g / mol; the terminal hydroxyl hyperbranched polyester B has a hydroxyl number of 20-24 / mol, a hydroxyl value of 500 mgKOH / g, and a molecular weight of 2600 g / mol; the terminal hydroxyl hyperbranched polyester C has a hydroxyl number of 10-12 / mol, a hydroxyl value of 260 mgKOH / g, and a molecular weight of 2500 g / mol.

[0013] The invention can improve the bending resistance of the coating agent on the surface of electrostatic copy paper by adding terminal hydroxyl hyperbranched polyester to the coating agent. The hydroxyl groups in the terminal hydroxyl hyperbranched polyester can undergo cross-linking reaction with other functional components such as modified epoxy resin to form a more compact and stable three-dimensional network structure. This high cross-linking density network structure can effectively resist external stress and improve the overall strength and durability of the coating.

[0014] Furthermore, the preparation method of the modified material comprises the following steps: (1) mixing cerium dioxide, titanium dioxide and carbon nanotubes in a weight ratio of 1: (0.5-0.7): (1.2-1.4) to obtain a mixture; (2) mixing silane coupling agent KH570, ethanol and water in a molar ratio of 1:(4-6):(3-5), and hydrolyzing at 30-35°C for 40-50 minutes to obtain a hydrolyzate; (3) Mix the mixture and the hydrolyzate in a weight ratio of 10:(13-15), heat to 100-110°C, stir and react for 60-70 minutes, continue to heat to 125-130°C, add 1 part by weight of triglycidyl isocyanurate, react for 60-80 minutes, and dry to obtain a modified material.

[0015] Furthermore, the particle size of the cerium dioxide is 30-50 nm, and the specific surface area is 20-40 m 2 / g; the particle size of the titanium dioxide is 10nm and the specific surface area is 30-50m 2 / g; the carbon nanotubes have an inner diameter of 10-20nm, a tube length of 5-15μm, and a specific surface area of ​​120-180m 2 / g.

[0016] The invention improves the compatibility and dispersibility in the system by modifying cerium dioxide, titanium dioxide and carbon nanotubes with flame retardant effect, and can improve the flame retardant performance of the flame retardant coating agent. , CNTs and CNTs each have different flame retardant mechanisms. Through reasonable proportioning and surface modification, the synergistic effect of multiple flame retardant mechanisms can be achieved. The surface modification of cerium dioxide, titanium dioxide and carbon nanotubes with flame retardant effect is performed. The present invention significantly improves the compatibility and dispersibility of these nanomaterials in the flame retardant coating. This improvement not only enhances the synergistic effect between the components, but also significantly improves the overall flame retardant performance of the coating through the combined effect of multiple flame retardant mechanisms. At the same time, the application of silane coupling agent KH570 and triglycidyl isocyanurate further enhances the crosslinking density and mechanical strength of the coating. At the same time, the wear resistance of the coating is improved.

[0017] When the present invention uses three specific parameters of terminal hydroxyl hyperbranched polyester and specific parameters of cerium dioxide, titanium dioxide and carbon nanotubes at the same time, the bending resistance of the coating agent on the surface of electrostatic copy paper under variable temperature conditions can be improved.

[0018] The present invention also provides a method for preparing a flame retardant coating agent for surface modification of wood and paper, comprising the following steps: (1) The preparation method of the modified epoxy resin is as follows: under light-proof conditions, mixing the raw materials of phase B, adding them to phase A, stirring and mixing, and obtaining the modified epoxy resin; (2) The modified epoxy resin and other components are uniformly mixed to obtain a flame retardant coating agent for surface modification of wood and paper.

[0019] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention can improve the adhesion of the flame retardant coating agent on the surface of electrostatic copy paper by modifying DGEBA.

[0020] 2. The present invention can improve the bending resistance of the coating agent on the surface of electrostatic copy paper by adding terminal hydroxyl hyperbranched polyester to the coating agent.

[0021] 3. The present invention improves the compatibility and dispersibility in the system by modifying the cerium dioxide, titanium dioxide and carbon nanotubes with flame retardant effect, thereby improving the flame retardant performance of the flame retardant coating and the wear resistance of the coating.

[0022] 4. When three specific parameters of terminal hydroxyl hyperbranched polyesters and specific parameters of cerium dioxide, titanium dioxide and carbon nanotubes are compounded, the bending resistance of the coating agent on the surface of electrostatic copy paper under variable temperature conditions can be improved. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The raw materials used in the following examples of the present invention are all commercially available products: DGEBA resin is E51 type epoxy resin purchased from Jinan Sunny Chemical Technology Co., Ltd.

[0025] Isocyanate curing agent, brand Evonik, model VESTAGONB1530.

[0026] 184 initiator, CAS No. 947-19-3.

[0027] TPO, CAS No. 1456769-77-9.

[0028] The brand of polyetheramine epoxy thermal curing agent is D230, brand: Huntsman. Example 1

[0029] This embodiment provides a flame retardant coating agent for surface modification of wood and paper, comprising the following components in parts by weight: 75 parts of modified epoxy resin, 27 parts of terminal hydroxyl hyperbranched polyester, 13 parts of modified material and 25 parts of isocyanate curing agent; The raw materials for preparing the modified epoxy resin are phase A and phase B; wherein phase A is DEM resin, and phase B is a free radical photoinitiator and a polyetheramine epoxy thermal curing agent; The raw materials for preparing the DEM resin are: DGEBA resin, methacrylic acid, glycidyl methacrylate, p-hydroxyanisole, and benzyltriethylammonium chloride; the molar ratio of the DGEBA resin to methacrylic acid is 2:1; the amount of glycidyl methacrylate is 76% of the mass of the DGEBA resin; the amount of p-hydroxyanisole is 0.3% of the mass of the DGEBA resin; and the amount of benzyltriethylammonium chloride is 0.15% of the mass of the DGEBA resin.

[0030] The preparation method of the DEM resin comprises: firstly adding DGEBA resin and p-hydroxyanisole into a four-necked flask, then introducing nitrogen and heating to 62°C, pouring methacrylic acid into a constant pressure funnel, and dripping it into the four-necked flask, while slowly heating to 117°C, adding benzyltriethylammonium chloride to react for 2.5 hours, measuring the acid value of the system every 35 minutes during the reaction, until the acid value of the system drops below 3 mgKOH / g, and the reaction is terminated; cooling to 42°C, adding glycidyl methacrylate, fully stirring for 7 minutes, and then discharging the material to obtain the DEM resin.

[0031] The free radical photoinitiator is 184 initiator and TPO; the mass ratio of 184 initiator to DEM resin is 0.6:100; the mass ratio of TPO to DEM resin is 0.6:100.

[0032] The grade of the polyetheramine epoxy thermal curing agent is D230, and the mass ratio of the polyetheramine epoxy thermal curing agent with the grade of D230 to the DEM resin is 23:100.

[0033] The terminal hydroxyl hyperbranched polyester includes terminal hydroxyl hyperbranched polyester A, terminal hydroxyl hyperbranched polyester B and terminal hydroxyl hyperbranched polyester C in a weight ratio of 1:1.3:0.5; the terminal hydroxyl hyperbranched polyester A has a hydroxyl number of 10-12 / mol, a hydroxyl value of 600mgKOH / g, a molecular weight of 1100g / mol, and a model H102; the terminal hydroxyl hyperbranched polyester B has a hydroxyl number of 20-24 / mol, a hydroxyl value of 500mgKOH / g, a molecular weight of 2600g / mol, and a model H203; the terminal hydroxyl hyperbranched polyester C has a hydroxyl number of 10-12 / mol, a hydroxyl value of 260mgKOH / g, a molecular weight of 2500g / mol, and a model H302. It was purchased from Wuhan Hyperbranched Resin Technology Co., Ltd.

[0034] The preparation method of the modified material comprises the following steps: (1) mixing cerium dioxide, titanium dioxide and carbon nanotubes in a weight ratio of 1:0.6:1.3 to obtain a mixture; (2) Mixing silane coupling agent KH570, ethanol and water in a molar ratio of 1:5:4, and hydrolyzing at 32°C for 45 minutes to obtain a hydrolyzate; (3) The mixture and the hydrolyzate in a weight ratio of 10:13 were mixed, the temperature was raised to 105°C, and the mixture was stirred for reaction for 65 minutes. The temperature was further raised to 128°C, 1 part by weight of triglycidyl isocyanurate was added, the mixture was reacted for 70 minutes, and the mixture was dried to obtain a modified material.

[0035] The particle size of the cerium dioxide is 30-50nm, and the specific surface area is 20-40m 2 / g, model ZT-Ce03, Zhejiang Zhiti Nano Micro New Materials Co., Ltd.; the particle size of the titanium dioxide is 10nm, and the specific surface area is 30-50m 2 / g, model DK-TiO2-A10, Beijing Dekedaojin Technology Co., Ltd.; the carbon nanotubes have an inner diameter of 10-20nm, a tube length of 5-15μm, and a specific surface area of ​​120-180m 2 / g. Purchased from Shanghai Maoguo Nanotechnology Co., Ltd.

[0036] The preparation method of the flame retardant coating agent for surface modification of wood and paper comprises the following steps: (1) The preparation method of the modified epoxy resin is as follows: under light-proof conditions, mixing the raw materials of phase B, adding them to phase A, stirring and mixing, and obtaining the modified epoxy resin; (2) The modified epoxy resin and other components are uniformly mixed to obtain a flame retardant coating agent for surface modification of wood and paper. Example 2

[0037] This embodiment provides a flame retardant coating agent for surface modification of wood and paper, comprising the following components in parts by weight: 70 parts of modified epoxy resin, 30 parts of terminal hydroxyl hyperbranched polyester, 10 parts of modified material and 30 parts of isocyanate curing agent; The raw materials for preparing the modified epoxy resin are phase A and phase B; wherein phase A is DEM resin, and phase B is a free radical photoinitiator and a polyetheramine epoxy thermal curing agent; The raw materials for preparing the DEM resin are: DGEBA resin, methacrylic acid, glycidyl methacrylate, p-hydroxyanisole, and benzyltriethylammonium chloride; the molar ratio of the DGEBA resin to methacrylic acid is 1.8:1; the amount of glycidyl methacrylate is 79% of the mass of the DGEBA resin; the amount of p-hydroxyanisole is 0.2% of the mass of the DGEBA resin; and the amount of benzyltriethylammonium chloride is 0.2% of the mass of the DGEBA resin.

[0038] The preparation method of the DEM resin comprises: firstly adding DGEBA resin and p-hydroxyanisole into a four-necked flask, then introducing nitrogen and heating to 65°C, pouring methacrylic acid into a constant pressure funnel, and dripping it into the four-necked flask, while slowly heating to 120°C, adding benzyltriethylammonium chloride to react for 2h, measuring the acid value of the system every 40min during the reaction, until the acid value of the system drops below 3mgKOH / g, and the reaction is terminated; cooling to 40°C, adding glycidyl methacrylate, fully stirring for 10min, and then discharging to obtain the DEM resin.

[0039] The free radical photoinitiator is 184 initiator and TPO; the mass ratio of 184 initiator to DEM resin is 0.7:100; the mass ratio of TPO to DEM resin is 0.7:100.

[0040] The grade of the polyetheramine epoxy thermal curing agent is D230, and the mass ratio of the polyetheramine epoxy thermal curing agent with the grade of D230 to the DEM resin is 21:100.

[0041] The terminal hydroxyl hyperbranched polyester includes terminal hydroxyl hyperbranched polyester A, terminal hydroxyl hyperbranched polyester B and terminal hydroxyl hyperbranched polyester C in a weight ratio of 1:1.2:0.4; the terminal hydroxyl hyperbranched polyester A has a hydroxyl number of 10-12 / mol, a hydroxyl value of 600mgKOH / g, a molecular weight of 1100g / mol, and a model H102; the terminal hydroxyl hyperbranched polyester B has a hydroxyl number of 20-24 / mol, a hydroxyl value of 500mgKOH / g, a molecular weight of 2600g / mol, and a model H203; the terminal hydroxyl hyperbranched polyester C has a hydroxyl number of 10-12 / mol, a hydroxyl value of 260mgKOH / g, a molecular weight of 2500g / mol, and a model H302. It was purchased from Wuhan Hyperbranched Resin Technology Co., Ltd.

[0042] The preparation method of the modified material comprises the following steps: (1) mixing cerium dioxide, titanium dioxide and carbon nanotubes in a weight ratio of 1:0.5:1.2 to obtain a mixture; (2) Mix silane coupling agent KH570, ethanol and water in a molar ratio of 1:4:5, and hydrolyze at 30°C for 50 minutes to obtain a hydrolyzate; (3) The mixture and the hydrolyzate in a weight ratio of 2:3 were mixed, the temperature was raised to 110°C, and the mixture was stirred for reaction for 60 minutes. The temperature was further raised to 130°C, 1 part by weight of triglycidyl isocyanurate was added, the mixture was reacted for 80 minutes, and the mixture was dried to obtain a modified material.

[0043] The particle size of the cerium dioxide is 30-50nm, and the specific surface area is 20-40m 2 / g, model ZT-Ce03, Zhejiang Zhiti Nano Micro New Materials Co., Ltd.; the particle size of the titanium dioxide is 10nm, and the specific surface area is 30-50m 2 / g, model DK-TiO2-A10, Beijing Dekedaojin Technology Co., Ltd.; the carbon nanotubes have an inner diameter of 10-20nm, a tube length of 5-15μm, and a specific surface area of ​​120-180m 2 / g. Purchased from Shanghai Maoguo Nanotechnology Co., Ltd.

[0044] The preparation method of the flame retardant coating agent for surface modification of wood and paper comprises the following steps: (1) The preparation method of the modified epoxy resin is as follows: under light-proof conditions, mixing the raw materials of phase B, adding them to phase A, stirring and mixing, and obtaining the modified epoxy resin; (2) The modified epoxy resin and other components are uniformly mixed to obtain a flame retardant coating agent for surface modification of wood and paper.

[0045] Comparative Example 1 The difference between this comparative example and Example 1 is that the modified epoxy resin is replaced by DGEBA resin. DGEBA resin is E51 epoxy resin purchased from Jinan Sunny Chemical Technology Co., Ltd.

[0046] Comparative Example 2 The difference between this comparative example and Example 1 is that the terminal hydroxyl hyperbranched polyester comprises terminal hydroxyl hyperbranched polyester A, terminal hydroxyl hyperbranched polyester B and terminal hydroxyl hyperbranched polyester C in a weight ratio of 1:1:1; the terminal hydroxyl hyperbranched polyester A has a hydroxyl number of 10-12 / mol, a hydroxyl value of 600mgKOH / g, and a molecular weight of 1100g / mol; the terminal hydroxyl hyperbranched polyester B has a hydroxyl number of 20-24 / mol, a hydroxyl value of 500mgKOH / g, and a molecular weight of 2600g / mol; the terminal hydroxyl hyperbranched polyester C has a hydroxyl number of 10-12 / mol, a hydroxyl value of 260mgKOH / g, and a molecular weight of 2500g / mol.

[0047] Comparative Example 3 The difference between this comparative example and Example 1 is that the terminal hydroxyl hyperbranched polyester includes terminal hydroxyl hyperbranched polyester A, terminal hydroxyl hyperbranched polyester B and terminal hydroxyl hyperbranched polyester C in a weight ratio of 1:1.3:0.5; the terminal hydroxyl hyperbranched polyester A has a hydroxyl number of 5-7 / mol, a hydroxyl value of 670mgKOH / g, a molecular weight of 500g / mol, and a model H101; the terminal hydroxyl hyperbranched polyester B has a hydroxyl number of 20-24 / mol, a hydroxyl value of 240mgKOH / g, a molecular weight of 5500g / mol, and a model H303; the terminal hydroxyl hyperbranched polyester C has a hydroxyl number of 40-45 / mol, a hydroxyl value of 230mgKOH / g, a molecular weight of 11500g / mol, and a model H304. Purchased from Wuhan Hyperbranched Resin Technology Co., Ltd.

[0048] Comparative Example 4 The difference between this comparative example and Example 1 is that only one type of terminal hydroxyl hyperbranched polyester is used, with a hydroxyl number of 20-24 / mol, a hydroxyl value of 500 mgKOH / g, a molecular weight of 2600 g / mol, and a model of H203, which is purchased from Wuhan Hyperbranched Resin Technology Co., Ltd.

[0049] Comparative Example 5 The difference between this comparative example and Example 1 is that cerium dioxide, titanium dioxide and carbon nanotubes are mixed in a weight ratio of 1:1:1 to obtain a mixture.

[0050] Comparative Example 6 The difference between this comparative example and Example 1 is that the particle size of the cerium dioxide is 0.2-0.3 μm, and the specific surface area is 10-20 m 2 / g, model ZT-Ce02, Zhejiang Zhiti Nano Micro New Materials Co., Ltd.; the particle size of the titanium dioxide is 60nm, and the specific surface area is 20-30m 2 / g, model DK-TiO2-A60, Beijing Dekedaojin Technology Co., Ltd.; the carbon nanotubes have an inner diameter of 15-30nm, a tube length of 10-30μm, and a specific surface area of ​​50-80m 2 / g. Purchased from Xianfeng Nano.

[0051] Performance Testing The electrostatic copy paper used in the test (Electrostatic Copy Paper (GB / T22339-2008) has a basis weight of 70.0 g / m 2 , tensile strength 18.65MPa, 8.9% elongation at break), as the substrate prepared into the same size of 70×210mm. The coating agent drop amount is 0.18mL / cm 2 , spray with a spray gun, let it stand for even coating, and then store it at room temperature 25°C for 12 hours to obtain a test paper sample.

[0052] (1) Use methane flame (about 500℃) to test the sample horizontally and evaluate the total burning time of the sample. The national standard for flame retardant paper is to test the flame retardant properties and determine the after-flame time. The national standard for flame retardant paper stipulates that the average after-flame time is ≤ 5s.

[0053] (2) Adhesion is measured in accordance with GBT9286-2021.

[0054] (3) The wear resistance of the coating was measured with reference to GB / T1768-2006 “Determination of abrasion resistance of paints and varnishes: Rotating rubber grinding wheel method”.

[0055] (4) Flexing resistance test: Test the test paper samples on the flexing resistance test machine and set the test flexing times to 10,000 times. Observe whether the test paper samples have obvious cracks and whether there is any delamination at the folds. If there is no obvious crack and no delamination at the folds, it is considered qualified, otherwise it is considered unqualified.

[0056] (5) Temperature flex test: Place the test paper sample at -10℃, 25℃ and 50℃ for 10 days respectively as one cycle, and test 3 cycles in total. Then perform the flex test at room temperature to observe whether the test paper sample has obvious cracks and whether there is delamination at the crease. If there is no obvious crack and no delamination at the crease, it is qualified, otherwise it is unqualified.

[0057] Table 1 Performance test results Afterburning time Adhesion Wear resistance mg / 1000r Flexure resistance test Variable temperature flexural resistance test Example 1 4.2 Level 1 6.6 qualified qualified Example 2 4.6 Level 1 6.8 qualified qualified Comparative Example 1 4.4 Level 2 7.3 Failure Failure Comparative Example 2 4.3 Level 1 7.0 Failure Failure Comparative Example 3 4.4 Level 1 6.9 Failure Failure Comparative Example 4 4.5 Level 2 7.1 Failure Failure Comparative Example 5 6.2 Level 2 7.9 qualified Failure Comparative Example 6 5.7 Level 2 7.5 qualified Failure From the above performance test results, it can be seen that the flame retardant coating agents of Examples 1-2 have good coating effects on the surface of electrostatic copy paper, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic compounding of the components.

[0058] However, the comparative examples are obviously inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, DGEBA is not modified, and the adhesion of the flame retardant coating agent on the surface of electrostatic copy paper decreases. In comparative example 2, the ratio of terminal hydroxyl hyperbranched polyester is different, the parameters of the three terminal hydroxyl hyperbranched polyesters in comparative example 3 are different, and only one terminal hydroxyl hyperbranched polyester is used in comparative example 4. The bending resistance of the coating agent on the surface of electrostatic copy paper decreases, and it can be found that when terminal hydroxyl hyperbranched polyesters with different parameters are used, the bending resistance under variable temperature decreases. In comparative example 5, the ratio of cerium dioxide, titanium dioxide and carbon nanotubes, and the parameters of cerium dioxide, titanium dioxide and carbon nanotubes in comparative example 6 are different, and the flame retardant performance of the flame retardant coating agent decreases, and the wear resistance decreases. Moreover, the parameters of cerium dioxide, titanium dioxide and carbon nanotubes are different, and the bending resistance under variable temperature decreases. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0059] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A flame retardant coating agent for surface modification of wood and paper, characterized in that: The invention comprises the following components in parts by weight: 70-80 parts of modified epoxy resin, 25-30 parts of terminal hydroxyl hyperbranched polyester, 10-15 parts of modified material and 20-30 parts of isocyanate curing agent; The raw materials for preparing the modified epoxy resin are phase A and phase B; wherein phase A is DEM resin, and phase B is a free radical photoinitiator and a polyetheramine epoxy thermal curing agent; The raw materials for preparing the DEM resin are: DGEBA resin, methacrylic acid, glycidyl methacrylate, p-hydroxyanisole, and benzyltriethylammonium chloride; the molar ratio of the DGEBA resin to methacrylic acid is (1.8-2.2):1; the amount of p-hydroxyanisole is 0.2-0.4% of the mass of the DGEBA resin; and the amount of benzyltriethylammonium chloride is 0.1-0.2% of the mass of the DGEBA resin.

2. The flame retardant coating agent for surface modification of wood and paper according to claim 1, characterized in that: The usage of glycidyl methacrylate is 75-79% of the mass of DGEBA resin.

3. The flame retardant coating agent for surface modification of wood and paper according to claim 1, characterized in that: The preparation method of the DEM resin comprises: firstly adding DGEBA resin and p-hydroxyanisole into a four-necked flask, then introducing nitrogen and heating to 60-65°C, pouring methacrylic acid into a constant pressure funnel, and dripping it into the four-necked flask, while slowly heating to 115-120°C, adding benzyltriethylammonium chloride to react for 2-3h, measuring the acid value of the system every 30-40min during the reaction, until the acid value of the system drops below 3mgKOH / g, and the reaction is terminated; cooling to 40-45°C, adding glycidyl methacrylate, fully stirring for 5-10min, and then discharging to obtain the DEM resin.

4. The flame retardant coating agent for surface modification of wood and paper according to claim 1, characterized in that: The free radical photoinitiator is 184 initiator and TPO.

5. The flame retardant coating agent for surface modification of wood and paper according to claim 4, characterized in that: The mass ratio of 184 initiator and DEM resin is (0.5-0.7):

100.

6. The flame retardant coating agent for surface modification of wood and paper according to claim 5, characterized in that: The mass ratio of TPO and DEM resin is (0.5-0.7):

100.

7. The flame retardant coating agent for surface modification of wood and paper according to claim 1, characterized in that: The terminal hydroxyl hyperbranched polyester comprises a terminal hydroxyl hyperbranched polyester A, a terminal hydroxyl hyperbranched polyester B and a terminal hydroxyl hyperbranched polyester C in a weight ratio of 1: (1.2-1.4): (0.4-0.6); the terminal hydroxyl hyperbranched polyester A has a hydroxyl number of 10-12 / mol, a hydroxyl value of 600 mgKOH / g and a molecular weight of 1100 g / mol; the terminal hydroxyl hyperbranched polyester B has a hydroxyl number of 20-24 / mol, a hydroxyl value of 500 mgKOH / g and a molecular weight of 2600 g / mol; the terminal hydroxyl hyperbranched polyester C has a hydroxyl number of 10-12 / mol, a hydroxyl value of 260 mgKOH / g and a molecular weight of 2500 g / mol.

8. The flame retardant coating agent for surface modification of wood and paper according to claim 1, characterized in that: The preparation method of the modified material comprises the following steps: (1) mixing cerium dioxide, titanium dioxide and carbon nanotubes in a weight ratio of 1: (0.5-0.7): (1.2-1.4) to obtain a mixture; (2) mixing silane coupling agent KH570, ethanol and water in a molar ratio of 1:(4-6):(3-5), and hydrolyzing at 30-35°C for 40-50 minutes to obtain a hydrolyzate; (3) Mix the mixture and the hydrolyzate in a weight ratio of 10:(13-15), heat to 100-110°C, stir and react for 60-70 minutes, continue to heat to 125-130°C, add 1 part by weight of triglycidyl isocyanurate, react for 60-80 minutes, and dry to obtain a modified material.

9. The flame retardant coating agent for surface modification of wood and paper according to claim 8, characterized in that: The particle size of the cerium dioxide is 30-50nm, and the specific surface area is 20-40m 2 / g; the particle size of the titanium dioxide is 10nm and the specific surface area is 30-50m 2 / g; the inner diameter of the carbon nanotube is 10-20nm, the tube length is 5-15μm, and the specific surface area is 120-180m 2 / g.

10. A method for preparing a flame retardant coating agent for surface modification of wood and paper according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) The preparation method of the modified epoxy resin is as follows: under light-proof conditions, mixing the raw materials of phase B, adding them to phase A, stirring and mixing, and obtaining the modified epoxy resin; (2) The modified epoxy resin and other components are uniformly mixed to obtain a flame retardant coating agent for surface modification of wood and paper.

Citation Information

Patent Citations

  • Priming free UV curable varnish and preparation method and applications thereof

    CN108411695A

  • Paper flame retardant with high film-forming property and preparation method thereof

    CN108978341A

  • Preparation method of flame-retardant coating material

    CN109762444A

  • Halogen-free flame-retardant cationic electro-deposition coating

    CN112210273A

  • High-performance flame-retardant antistatic powder coating and preparation method thereof

    CN114250027A